Motor learning dysfunction and its association with neurotransmitters and gut microbiota dysbiosis in hepatic encephalopathy mice - Yunqi SHAN; Haidan DENG; Baojun SHAN; Jiaying HUANG; Xinshu FENG; Xiaoming SUN (KeAi Communications Co., Ltd., 2022)
[Abstract]: Objective: This study aims to investigate the potential mechanisms underlying motor learning dysfunction in hepatic encephalopathy (HE) mice using gut microbiota and neurochemicals. Methods: C57BL/6 mice were intraperitoneally treated with thioacetamide to induce the HE model. Cytokines of TNF-α and ammonia in serum and motor cortex were tested using the ELISA kit. Rota-rod was used to assess the motor learning behavior of HE mice. The 16S rDNA analysis revealed gut microbiota species and abundance changes in HE mice. The 26 neurochemicals of control and HE mice were quantified and analyzed with different microbiota using the UPLC-TQ-MS technique. Results: LEfSe analysis revealed that 25 genera differed significantly between healthy and HE mice. Correlation analysis revealed that the Escherichia_Shigella, Allobaculum, and Muribaculaceae were associated with higher adrenaline levels of hydrochloride, 4-aminobytyric acid, and L-glutamic acid and lower levels of L-histidine and histamine. Conclusion: The neurotransmitter changes in motor cortex have some relationship with gut microbiota disturbances. This correlation may pave the way to explain the cognitive and motor learning dysfunction in HE mice.